Generation of an enhancer-driven gene expression viral tool specific to dentate granule cell-types through direct hippocampal injection - Potenza, Maria Letizia; Blankvoort, Stefan; Carvalho, Miguel M.; Grimstvedt, Joachim S.; Di Maria, Valentina; Moan, Kristian; Nair, Rajeevkumar Raveendran; Flatset, Marcus S.; Zhang, Qiangwei; Thomas, Laurent F.; Pauzin, Francois P.; Da Silva Mazzarini Baldinotti, Rodolfo; et al. (Frontiers in Neuroscience, 2024)
The mammalian brain contains an enormous number of neurons, that are all intricately connected to form complex neuronal circuits. By investigating properties such as the genetic profile, the morphology and the electrophysiological properties, hundreds of cell-types have been identified. A key aspect of studying brain function on a circuit level is the ability to target specific cell types, but this necessitates sophisticated molecular and genetic tools. Here, we contribute to the ever-expanding toolkit of genetic targeting approaches, by utilizing Enhancer-Driven Gene Expression (EDGE) technology to create recombinant adeno-associated virus (rAAV) based tools that allow specific targeting of cell populations in the hippocampal formation of wild type mice. We also demonstrate the applicability of our tool in wild type rats, emphasizing the versatility of this technology in crossspecies studies. Cell-type specific targeting in wild-type animals, especially species for which transgenic lines are not available, is a major goal in neuroscience. In this manuscript, we discuss the generation and use of EDGE rAAV-based tools, demonstrate these ideas with a novel EDGE-rAAV that differentiates between hippocampal cell types, and provide genomic data to aid others in expanding the toolkit to specifically label neuronal cell-types of interest.